2003
DOI: 10.1152/ajpendo.00410.2002
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive and specific assay for determination of IGF-I bioactivity in human serum

Abstract: At present, the circulating bioactivity of insulin-like growth factor I (IGF-I) is estimated by immunological measurements of IGF-I levels. However, immunoassays ignore the modifying effects of the IGF-binding proteins (IGFBPs) on the interaction between IGF-I and the IGF-I receptor (IGF-IR). Therefore, we developed an IGF-I kinase receptor activation assay (KIRA) based on cells transfected with the human IGF-IR gene. The bioassay was sensitive (detection limit 0.08 μg/l), specific (cross-reactivity of insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
172
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 160 publications
(176 citation statements)
references
References 22 publications
4
172
0
Order By: Relevance
“…The study was approved by the Local Ethical Committee. Bioactive IGF1 was determined by the KIRA assay based on human embryonic renal cells (EBNA 293) transfected with the human IGF1R gene (21), with modifications as previously published (24). Total serum IGF1 was determined by time-resolved immunofluorometric assay with modifications as recently published (24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was approved by the Local Ethical Committee. Bioactive IGF1 was determined by the KIRA assay based on human embryonic renal cells (EBNA 293) transfected with the human IGF1R gene (21), with modifications as previously published (24). Total serum IGF1 was determined by time-resolved immunofluorometric assay with modifications as recently published (24).…”
Section: Methodsmentioning
confidence: 99%
“…phosphorylate) the IGF1 receptor (IGF1R) in vitro (i.e. bioactive IGF1) (21). Subsequent studies have demonstrated that bioactive IGF1 is inversely correlated with age (22), significantly higher in females compared with males (23), and positively correlated with IGF1 as measured by immunoassay (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive IGF1 was measured by the IGF1 kinase receptor activator assay based on human embryonic renal cells (EBNA 293) transfected with the human IGF1R gene (23). In brief, cultured cells were stimulated with either IGF1 standards or serum samples (diluted tenfold) from the subjects in this study.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Intra-and inter-assay coefficient of variation (CV) averaged 5 and 10% respectively (15). Bioactive IGF1 was determined by a cell-based kinase receptor activation assay (KIRA) based on human embryonic cells transfected with the human IGF1 receptor (IGF1R) gene (16). The bioassay determines the ability of serum IGF to phosphorylate the IGF1R in vitro, and takes into account the presence of the IGFBPs and their ability to modify IGF1R activation.…”
Section: Assaysmentioning
confidence: 99%